Anti-crisis management in small and medium business - Мареніченко, В. В. (Scientific Progress & Innovations, 2012)
Actuality of study in crisis management system for small and medium business in Ukraine has been substantiated. The major advantages of small and medium enterprises have been analyzed. Studied Anti-crisis measures which should be introduced at the state level have been studied. The most vulnerable areas of the business where you want to apply measures of prevention and resist the crisis have been discovered. Influence factors on the decline of small and medium enterprises and the system of anti-crisis measures, as a mechanism for increasing the efficiency of the enterprise have been determined.